Crystal structure and microstructure of synthetic hexagonal magnesium–cobalt cordierite solid solutions (Mg2−2xCo2xAl4Si5O18). (26th February 2013) - Serrano, Francisco Javier; Montoya, Noemí; Pizarro, José Luis; Reventós, María Mercedes; Kojdecki, Marek Andrzej; Amigó, José María; Alarcón, Javier
<x xml:space="preserve">Abstract</x> Co2+‐containing cordierite glasses, of nominal compositions (Mg1−xCox)2Al4Si5O18 (with x = 0, 0.2, 0.4, 0.6, 0.8 and 1), were prepared by melting colloidal gel precursors. After isothermal heating at 1273 K for around 28 h, a single‐phase α‐cordierite (high‐temperature hexagonal polymorph) was synthesized. All materials were investigated using X‐ray powder diffraction and field‐emission scanning electron microscopy. The crystal structure and microstructure were determined from X‐ray diffraction patterns. Rietveld refinement confirmed the formation of magnesium–cobalt cordierite solid solutions. The unit‐cell volume increased with the increase of cobalt content in the starting glass. The crystalline microstructure of the cordierites was interpreted using a mathematical model of a polycrystalline material and characterized by prevalent crystallite shape, volume‐weighted crystallite size distribution and second‐order crystalline lattice‐strain distribution. Hexagonal prismatic was the prevalent shape of α‐cordierite crystallites. Bimodality in the size distribution was observed and interpreted as a consequence of two paths of the crystallization: the nucleation from glass of μ‐cordierite, which transformed into α‐cordierite with annealing, or the nucleation of α‐cordierite directly from glass at high temperatures. Scanning electron microscopy images agreed well with crystalline microstructure characteristics determined from the X‐ray diffraction line‐profile analysis.